Some Characteristics of Changes in the Axillary Lymph Nodes without Metastases After Chemotherapy in Patients with Mammary Gland Cancer - I. V. Maiborodin; V. I. Maiborodina; E. V. Babayants; D. N. Strunkin; V. G. Sisakyan; N. M. Kolotova (Антибиотики и Химиотерапия)
Light microscopy of the axillary lymph nodes in 74 relatively healthy women and in 186 patients with mammary gland cancer revealed that the lymph nodes of10.8% of the patients contained no substantia medullaris: the tractus pulposus and cerebral sinuses were replaced by various types of the connective tissue. Similar signs in the relatively healthy women were much rarer (5.4%). The frequency of the sclerotic transformation was shown to be not dependent on the neoadjuvant chemotherapy of the mammary gland cancer but increased with aging of the subjects. After the use of polychemotherapy followed by long-term traumatic surginal interventions, tissue detritus and blood formed elements were detectable in the sinus system of the regional lymph nodes.